Pathogenicity test bacteria from Oreochromis niloticus and Clarias gariepinus aquaculture ponds - Hardi, Esti Handayani; Halim, Aldi M.; Nugroho, Rudy Agung; Mawardi, Mira; Isnansetyo, Alim; Mariana Lusiastuti, Angela; Rahayu, Widianingsih; Niklani, Andi; Saptiani, Gina (Jurnal Akuakultur Indonesia, 2023)
Present research aimed to examine the pathogenicity opportunities of some bacteria which were isolated from freshwater aquaculture ponds to some fish Oreochromis niloticus, Clarias gariepinus, and Pangasius pangasius. The bacteria were isolated from the water and feces of O. niloticus and C. gariepinus aquaculture in Samarinda, which were identified as Escherichia coli, Enterobacter cloacae, and Enterobacter amnigenus. An 0.1 mL-1 of each bacteria was intramuscular injection and evaluated the clinical signs, eksternal pathology, and fish mortality. The freshwater fish using in this research were Oreochromis niloticus, Clarias gariepinus, and Pangasius pangasius with size 10-15 g from Loa Kulu, Kutai Kartanegara Regency, East Kalimantan, Indonesia. The result showed that each bacteria caused mortality in fish: E. coli bacteria caused fish mortality 23.33-66.67%; E. cloacae 10.00 to 90.00%; and E. amnigenus by 3.33-56.67%. The average death time of E. coli and E. amnigenus in all three fish were under 48 hours, while E. cloacae caused mortality less than 48 hours in C. gariepinus and P. pangasius. In conclusion, E. coli, E. cloacae, and E. amnigenus are putative pathogenic bacterium in O. niloticus, C. gariepinus, and P. pangasius.